Multimodal Therapeutic Effects of Neural Precursor Cells Derived from Human-Induced Pluripotent Stem Cells through Episomal Plasmid-Based Reprogramming in a Rodent Model of Ischemic Stroke. (23rd March 2020) - Oh, Seung-Hun; Jeong, Yong-Woo; Choi, Wankyu; Noh, Jeong-Eun; Lee, Suji; Kim, Hyun-Sook; Song, Jihwan
Abstract : Stem cell therapy is a promising option for treating functional deficits in the stroke-damaged brain. Induced pluripotent stem cells (iPSCs) are attractive sources for cell therapy as they can be efficiently differentiated into neural lineages. Episomal plasmids (EPs) containing reprogramming factors can induce nonviral, integration-free iPSCs. Thus, iPSCs generated by an EP-based reprogramming technique (ep-iPSCs) have an advantage over gene-integrating iPSCs for clinical applications. However, there are few studies regarding the in vivo efficacy of ep-iPSCs. In this study, we investigated the therapeutic potential of intracerebral transplantation of neural precursor cells differentiated from ep-iPSCs (ep-iPSC-NPCs) in a rodent stroke model. The ep-iPSC-NPCs were transplanted intracerebrally in a peri-infarct area in a rodent stroke model. Rats transplanted with fibroblasts and vehicle were used as controls. The ep-iPSC-NPC-transplanted animals exhibited functional improvements in behavioral and electrophysiological tests. A small proportion of ep-iPSC-NPCs were detected up to 12 weeks after transplantation and were differentiated into both neuronal and glial lineages. In addition, transplanted cells promoted endogenous brain repair, presumably via increased subventricular zone neurogenesis, and reduced poststroke inflammation and glial scar formation. Taken together, these results strongly suggest that intracerebral transplantation of ep-iPSC-NPCs is a useful therapeutic option to treat clinical stroke through multimodal therapeutic mechanisms.